The elderly and television viewing - Maniar, Avani; Joshi, Uma (Delhi : Authorspress, 2007)
Contributed papers presented at a seminar organized by Centre for Central Eurasian Studies, University of Mumbai in February-March 2005.
Includes bibliographical references and index
Keywords: Television broadcasting -- Social aspects; Television programs -- Evaluation; Television viewers